THE STUDY OF THE ACTIVATION OF MTORC1 AND ITS SUBSTRATE P70S6K INVOLVED IN TYPE 2 DIABETES MELLITUS AND ONCOGENETIC PROCESSES - Vatseba T. S.; Sokolova L. K.; Pushkarev V. V.; Kovzun O. I.; Pushkarev V. M.; Tronko M. D. (Eastern Ukrainian Medical Journal, 2020)
Introduction. Pathogenetic factors of diabetes may affect the activity of intracellular systems of oncogenesis and metabolism regulation, one of which is PI3K/Akt/mTORC1. Macrophages and lymphocytes are involved in the pathogenesis of diabetes and cancer. Detection of excessive activation of PI3K/Akt/mTORC1 components and substrates in these cells may indicate the need for additional correction of metabolic processes in patients with type 2 diabetes from the point of prevention of cancer. The aim: to study the activation of mTORC1 by determining the phosphorylation of PRAS40 and p70S6K1 in the leukocytes of patients with type 2 diabetes and cancer.Materials and methods. The study included women from the following groups: control group, patients with type 2 diabetes, cancer patients, patients with both diseases. The content of phosphorylated PRAS40 (phospho-T246) and p70S6K1 (phospho-T389) was determined using laboratory kits ELISA KNO0421 and ELISA 85-86053 of Invitrogen (USA). The protein concentration in the lysate was determined using a BCA Novagen protein assay kit (USA). Measurements were performed on a microplate reader (Bio-tek Instruments, USA) at a wavelength of 450 nm.Results. Significantly increased content of phosphorylated PRAS40 and p70S6K1 in leukocytes of patients with type 2 diabetes mellitus and cancer was detected. The number of positive phospho-PRAS40 tests in patients with diabetes was 83.3%, and in cancer patients - 66.7%. Was revealed the reduced content of phospho-PRAS40 in leukocytes of patients with a combination of diabetes and cancer.Conclusions. The increased amount of phosphorylated PRAS40 and p70S6K1 proves the activation of the studied signaling pathway by diabetes mellitus type 2. Its decrease by cancer and diabetes can be explained by the possible competing effects of the proteins that affect upstream regulators of these kinases or them directly.